(untitled) (Journal of Nepal Physical Society, 2024)
The structural and vibrational characteristics of tenofovir have been calculated from density functional theory (DFT) by implementing the theory B3LYP/3-21G basis set. Based on Fourier Transform infrared (FT-IR), Fourier Transform Raman (FT-Raman), the spectroscopic characteristics of the compound under investigation have been closely examined. With the use of molecular electrostatic potential (MEP) surface analysis and local reactivity descriptors, the charge distribution around the molecular system has been examined in order to distinguish the nucleophilic and electrophilic regions. The red regions in MEP map across P1-O5 and O4-H signify nucleophilic sites and the blue color across amine group indicate the electrophilic centers. Additionally, global reactivity descriptors based on the energy of highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) have been used in predicting the molecule’s chemical reactivity. The HOMO-LUMO gap is found to be 5.58 eV. The structural stability of compound based on donor and acceptor Lewis type orbital from natural bond orbital (NBO) analysis give the information that the transition LP(1) C15→ π*(N9-C18) has major role for stability of compound and gives the stabilization energy 114.43 kcal/mol. Similarly, structural analysis and quantum chemical computation techniques have been used to study the fundamental chemical reactive regions of the tenofovir molecule. The highest value of Fukui function (FF) fk– across C16 is (0.1467) which is prone to nucleophilic center in the compound and the highest FF fk+ ( 0.1787) across N10 predict the electrophilic site in the compound. These findings are essential for further research using vibrational spectroscopy on drug-target interactions.